“Jean Piaget’s Theory of Cognitive Development” : A Review - Chopra, Dr Sanjay (Innovative Research Thoughts, 2018)
Piaget's (1936) theory of cognitive development describes the process by which a child forms an internal representation of the external environment. He did not think that one's intellect was fixed, but rather that it grew as a consequence of biological maturation and contact with one's environment. In other words, he felt that intelligence developed through time rather than the other way around. During the 1920s, Piaget was employed by the Binet Institute, where he was responsible for generating French translations of English intelligence test questions. He found himself utterly enthralled by the reasons that students made to justify their erroneous solutions to questions that required the use of logical thinking. After hearing all of these incorrect responses, he came to the conclusion that adults and children think in very different ways.